(untitled) (PRÁXIS EM SAÚDE, 2026)
This is a descriptive and reflective experience report about the experience of two undergraduate physiotherapy students during extension activities at a Municipal Emergency Hospital in São Luís, Maranhão, Brazil. The practice took place through the Mexa-se Project, with an educational, social, and scientific focus. The actions involved the prevention of pressure injuries, early mobilization, and functional rehabilitation of trauma patients. The experience enabled the students to recognize the relevance of hospital physiotherapy in preventing complications, promoting functional recovery, and strengthening multiprofessional healthcare teamwork.